VARIABILITAS TIPE ARTEFAK SITUS PAROTO, SOPPENG: INDIKATOR KARAKTER BUDAYA - nfn Nasruddin (Balai Arkeologi Provinsi Sulawesi Selatan, 2001)
The research along Walennae River has been under working since 1946-1947, but until the present day the absolute chronology and human-cultural-supported has yet to be found. Based on fauna fossils and artifacts (tools stone) it was assumed that Walannae Valley has closely related with Pleistocene age. Many fossils are found along the. Walennae River from fauna species that hitherto no longer be found, such as dwarf stegodon. There are eight stone tools found associates with fauna which exposing cultural characters and activities that once has taken place in Soppeng, Paroto sites.